Atomically Controlled Processing for Dopant Segregation in CVD Si and Ge Epitaxial Growth. (1st January 2018) - Murota, Junichi; Yamamoto, Yuji; Costina, Ioan; Tillack, Bernd; Thanh, Vinh Le; Loo, Roger; Caymax, Matty
Abstract : High performance Si-based devices require atomically ordered interface of heterostructures and doping profiles as well as strain engineering due to the introduction of Ge into Si. In this work, dopant (P and B) segregation for in-situ doping in CVD Si and Ge epitaxial growth is investigated. The epitaxial growth of in-situ doped Si and Ge films either on Si (100) or on a few nm-thick Si0.5 Ge0.5 /Si (100) was performed at 550–555°C and 350°C, respectively. In the case of P doping, the P atoms segregate to the Si and the Ge surfaces and a part of them are incorporated into the grown Si and Ge cap layers. The P segregation during Si growth is larger than that during Ge growth. In the case of B doping, the B atoms scarcely segregate to the grown Si and Ge surfaces. Based on these experimental results, the in-situ doping processes are explained by the modified Langmuir-type adsorption and reaction scheme.